On extremal problems for symmetric disjoint domains - Bakhtin, A. K.; Bakhtina, G. P. (Ukrains’kyi Matematychnyi Zhurnal, 1997)
We study two extremal problems for the product of powers of conformal radii of symmetric disjoint domains.